Proceedings from Nourish Now: A science dialogue on improving adolescent health through nutrition - Mario G. Ferruzzi; Regan L. Bailey; Teresa A. Davis; Heather J. Leidy; Jamie I. Baum; Jill Castle; Angela De Leon; Eva C. Diaz; Victor L. Fulgoni; Carolyn Gunther; Leslie Kaplan; Bracha Kopstick; et al. (Critical Reviews in Food Science and Nutrition, 2026)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Timing and hydrological conditions associated with bigheaded carp movement past navigation dams on the upper Mississippi river - Jon M. Vallazza; Kyle J. Mosel; David M. Reineke; Ann L. Runstrom; James H. Larson; Brent C. Knights (Biological Invasions, 2021)

Development of a quantitative PCR method for screening ichthyoplankton samples for bigheaded carps - Andrea K. Fritts; Brent C. Knights; James H. Larson; Jon J. Amberg; Christopher M. Merkes; Tariq Tajjioui; Steven E. Butler; Matthew J. Diana; David H. Wahl; Michael J. Weber; John D. Waters (Biological Invasions, 2019)

Identification of Bighead Carp and Silver Carp early-life environments and inferring Lock and Dam 19 passage in the Upper Mississippi River: insights from otolith chemistry - Gregory W. Whitledge; Brent Knights; Jon Vallazza; James Larson; Michael J. Weber; James T. Lamer; Quinton E. Phelps; Jacob D. Norman (Biological Invasions, 2019)

Erratum to: Using a gradient in food quality to infer drivers of fatty acid content in two filter-feeding aquatic consumers - James H. Larson; William B. Richardson; Jon M. Vallazza; Lynn A. Bartsch; Michelle R. Bartsch (Aquatic Sciences, 2017)

Using a gradient in food quality to infer drivers of fatty acid content in two filter-feeding aquatic consumers - James H. Larson; William B. Richardson; Jon M. Vallazza; Lynn A. Bartsch; Michelle R. Bartsch (Aquatic Sciences, 2017)

Relationships Between Land Cover and Dissolved Organic Matter Change Along the River to Lake Transition - James H. Larson; Paul C. Frost; Marguerite A. Xenopoulos; Clayton J. Williams; Ana M. Morales-Williams; Jon M. Vallazza; John C. Nelson; William B. Richardson (Ecosystems, 2014)

Production of Homozygous Transgenic Rainbow Trout with Enhanced Disease Resistance - Pinwen Peter Chiou; Maria J. Chen; Chun-Mean Lin; Jenny Khoo; Jon Larson; Rich Holt; Jo-Ann Leong; Gary Thorgarrd; Thomas T. Chen (Marine Biotechnology, 2014)